Managing noninvasive recurrences after definitive treatment for muscle-invasive bladder cancer or high-grade upper tract urothelial carcinoma. Issue 5 (September 2015) - DiBianco, John Michael; George, Arvin K.; Su, Daniel; Agarwal, Piyush K.
<x xml:space="preserve">Abstract</x> Purpose of review Approximately 50% of patients with muscle invasive urothelial carcinoma will relapse with distant recurrence. Though rates of local recurrence after definitive therapy have improved, management remains a challenge. In this review, treatment strategies for this cohort are re-examined in an effort to enhance patient outcomes. Recent findings Urothelial carcinoma continues to demonstrate high rates of recurrence and low rates of survival. Similarly to the treatment of primary urothelial cancer, treatment of recurrence focuses on cytology, stage, and clinical characteristics. Current areas of interest have focused on identification and causes/predictors of recurrence. Summary Limited progress has been achieved in differentiating management of recurrent urothelial carcinoma from the treatment of primary urothelial carcinoma. However, there may be an increasing role for endoscopic and organ conserving therapies for carefully selected patients with recurrent noninvasive urothelial carcinoma. Identifying those at risk for early recurrence and early diagnosis of recurrence may be the most beneficial future strategies. The treatment regimen for noninvasive bladder recurrence after radical nephroureterectomy for upper tract urothelial carcinoma should include intravesical chemotherapy or Bacillus Calmette-Guerin to prevent further bladder recurrence or tumor progression. We do not advocate diversion sparing techniques for local recurrence after radical cystectomy. Metastasectomy for distant/metastatic urothelial carcinoma recurrence represents a promising area of future study.